RESPON PERTUMBUHAN DAN PRODUKSI KACANG HIJAU (Phaseolus radiatus L.) AKIBAT PENGGUNAAN PUPUK ORGANIK CAIR DAN PUPUK TSP - Wan Arfiani Barus; Hadriman Khair; Muhammad Anshar Siregar (AGRIUM: Jurnal Ilmu Pertanian, 2014)
The aim of this study was to determine the  growth and production responce of green bean by using of liquid organic fertilizer and TSP by   randomized block design (RBD) factorial with two factors under studied namely : liquid organic fertilizer (B) which consist of four standrd that  B0 = control, B1 = 5 cc / liter of water, B2 = 10 cc / liter of water and B3 = 15 cc / liter of water while fertilizer  TSP (T) which consist of three standard that  T0 = control, T1 = 15 g / plant, and T2 = 30 g / plants.  Liquid organic fertilizer as first factor and fertilizer TSP as a second factor.